Al Rawd al-Murbi' bisharh zad al-Mustaqni' Mukhtasar al-Muqni' fi al fiqh Imam al Sunnah Ahmad Ibn Hambal al Shaybani RA. - Sharfuddin Abi al Naja Musa Ibn Ahmad al Hajaw (Dar al-Kutub l-Ilmiyah, 1988)
ws.c.1-2